Simulating the Poverty Impact of Macroeconomic Shocks and Policies - Essama-Nssah, B. (World Bank, Washington, DC, 2012)
Developing countries face a host of macroeconomic challenges in the design and implementation of development strategies and policies. The importance of the underlying poverty and distributional issues creates a need for relevant and reliable ways of tracking the social impact of shocks and policies. This paper describes and demonstrates the use of a stylized framework for simulating the poverty implications of the Dutch disease, a change in the terms of trade and budgetary policy. The basic approach is to embed a Lorenz model of the size distribution of economic welfare in a general equilibrium model of an open economy. It is observed that, while aggregate welfare and poverty effects may be negligible, the structural and distributional impacts tend to be significant. The latter drive the political economy of policymaking and point to the need for an analytical framework that accounts for both the structural richness of the economy and the heterogeneity of the stakeholders